Deep learning with Azure : building and deploying artificial intelligence solutions on the Microsoft AI platform /: building and deploying artificial intelligence solutions on the Microsoft AI platform. (2018) - Salvaris, Mathew; Dean, Danielle; Tok, Wee-Hyong
No abstract available